LANGUAGE NORM AND VARIANT AS CRITERIA FOR PRESENTATIVE FUNCTION OF UTTERANCES IN SPECIALIZED TEXTS - SZUBERT, Rafał (Comparative Legilinguistics, 2017)
This paper deals with the issue of variants in language use and its consequences for the meaning transfer. Special attention shall be paid to the presentative function of an utterance. The author assumes that there is a sort of interrelation between the lexical language structure, its stability, conditions for its disfluencies and consequences resulting therefrom as well as langauge social funcion. A method which may be used to observe this interrelation may be the utterance analysis (the analysisi of communication units focused on their communication aim and correctness). The author presents the results of an experiment carried out among the students of German studies at the University of Wroclaw.